The effect of directed empathy on utilitarian moral judgments : the modulating role of selfishness and the intentionality of harm - Lim, Keith Ming Yeow (2017)
The present study aims to extend the literature on empathy and utilitarian moral judgments with two goals in mind: (1) to investigate the effect of directed empathy (i.e., empathic focus directed towards minority vs. majority victims) on utilitarian judgments; and (2) to test the moderating role of individual differences (e.g., trait selfishness) and contextual dependencies (e.g., intentionality of harm) in the relationship between directed empathy and utilitarian judgments. Two hundred and forty-three participants, aged between 20 to 77 years were recruited online via Amazon Mechanical Turk (MTurk) and randomly assigned to receive the directed empathy (minority vs. majority) induction. They completed a set of questionnaires measuring their traits of selfishness, empathy, deontologicalism, and utilitarianism, followed by responding to eight accidental and eight instrumental moral dilemmas that required a choice between: (1) killing one person to save more people (utilitarian judgment); and (2) not killing anyone and letting everyone die (deontological judgment). As expected, empathizing with majority victims increased utilitarian endorsements, while empathizing with minority victims reduced utilitarian endorsements. In addition, selfishness moderated the effect of directed empathy on utilitarian judgments, and this interaction was further qualified by moderation via intentionality of harm. Our findings underlie the nuances of evoked emotions (e.g., directed empathy), individual differences (e.g., selfishness), and contextual factors (e.g., harm intent) in altering the course of moral judgments. This, in turn, points to the need for existing theoretical frameworks to be revised in order to incorporate these nuanced determinants of moral judgments.